Answer/Step-by-step explanation:
The first equation is confusing so I'll solve both ways:
Addition
1. -4x + 2y = -12
4x + 8y = -24
-----------------------------
10y = -36
÷10 ÷10
--------------------
y = -3.6
4x + 8y = -24
4x + 8(-3.6) = -24
4x - 28.8 = -24
+28.8 +28.8
-----------------------------
4x = 4.8
÷4 ÷4
---------------------
x = 1.2
If the first equation is subtraction this is the solution:
2. -4x - 2y = -12
4x + 8y = -24
------------------------
6y = -36
÷6 ÷6
-------------------
y = -6
4x + 8y = -24
4x + 8(-6) = -24
4x - 48 = -24
+48 +48
---------------------
4x = 24
÷4 ÷4
-----------------
x = 6
(6, -6)
I hope this helps!